Serum glucose levels for predicting death in patients admitted to hospital for community acquired pneumonia: prospective cohort study - Lepper, Philipp Moritz; Eynatten, Maximilian von (The BMJ, 2012)
Objective: To examine whether acute dysglycaemia predicts death in people admitted to hospital with community acquired pneumonia. Design: Multicentre prospective cohort study. Setting: Hospitals and private practices in Germany, Switzerland, and Austria. Participants: 6891 patients with community acquired pneumonia included in the German community acquired pneumonia competence network (CAPNETZ) study between 2003 and 2009. Main outcome measures: Univariable and multivariable hazard ratios adjusted for sex, age, current smoking status, severity of community acquired pneumonia using the CRB-65 score (confusion, respiratory rate >30/min, systolic blood pressure ≤90 mm Hg or diastolic blood pressure ≤60 mm Hg, and age ≥65 years), and various comorbidities for death at 28, 90, and 180 days according to serum glucose levels on admission. Results: An increased serum glucose level at admission to hospital in participants with community acquired pneumonia and no pre-existing diabetes was a predictor of death at 28 and 90 days. Compared with participants with normal serum glucose levels on admission, those with mild acute hyperglycaemia (serum glucose concentration 6-10.99 mmol/L) had a significantly increased risk of death at 90 days (1.56, 95% confidence interval 1.22 to 2.01; P<0.001), and this risk increased to 2.37 (1.62 to 3.46; P<0.001) when serum glucose concentrations were ≥14 mmol/L. In sensitivity analyses the predictive value of serum glucose levels on admission for death was confirmed at 28 days and 90 days. Patients with pre-existing diabetes had a significantly increased overall mortality compared with those without diabetes (crude hazard ratio 2.47, 95% confidence interval 2.05 to 2.98; P<0.001). This outcome was not significantly affected by serum glucose levels on admission (P=0.18 for interaction). Conclusions: Serum glucose levels on admission to hospital can predict death in patients with community acquired pneumonia without pre-existing diabetes. Acute hyperglycaemia may therefore identify patients in need of intensified care to reduce the risk of death from community acquired pneumonia.